On-court physical demands and physiological aspects in elite team handball - Bojsen Michalsik, L. (Handball Sports Medicine, 2018)
Modern team handball match-play imposes substantial physical demands on elite players. However, only relatively limited knowledge seems to exist about the specific on-court working requirements in elite team handball. Thus, the overall purpose of this chapter is to give a brief overview of the present knowledge about the on-court physical demands placed on adult male and female elite team handball field players in relation to playing positions. In addition, it is also the aim to characterise the physiological aspects in elite team handball and to present an outline of the potential differences in the on-court physical demands in male vs. female adult elite team handball match-play. The activity pattern of goalkeepers is very much specialised and differs substantially from those of field players, and a description of the physical demands placed on goalkeepers is not included in this chapter. Gaining increased knowledge about the physical demands in elite team handball and the physiology of elite players provides the basis for improving the design, planning and implementation of optimal physical training in elite team handball players to increase playing performance and reduce fatigue and the number of overload injuries.